PENERAPAN SANKSI HUKUM BAGI PENGGUNA NARKOTIKA BERDASARKANUNDANG-UNDANG NARKOTIKA - Fathur Rachman (KEADILAN PROGRESIF, 2018)
Narcotics abuse is a dangerous thing that the handling of narcotics users is regulated in Law No. 35 of 2009 on narcotics, then the subject matter in this writing about the application of criminal sanctions for narcotics users in accordance with narcotics laws. Problem approach using normative juridical approach (legal research). If Narcotics Misuse can be proven or proven to be a victim of Narcotics abuse, such Abuse is obliged to undergo medical rehabilitation and social rehabilitation. Prevention and prevention of narcotic abuse is done maximally Narcotics Misuse must undergo medical rehabilitation and social rehabilitation.